The Effect of Mutualization and Collateralization on Credit Default Swaps Premium - Rojas Cama, Freddy Arnaldo (2025)
This paper examines the effect of collateralization and mutualization of losses on credit default swap (CDS) premiums in the context of high counterparty risk operating through an opaque derivatives market. This setup shows that clearing practices affect the size of positions, recovery rate and premium. This model not only has the benefit of being realistic in light of the causes and propagation of the Great Recession, but also in assessing clearing practices in a partial equilibrium. I follow closely the contributions of Koeppl and Monnet [38], Koeppl [35], Acharya and Bisin [1] and Stephens and Thompson [55]. I show that the premium is high when mutualization takes place as clearing policy; the new allocation is characterized by a high recovery rate and low risk premium as fully insured contracts spread significantly relative to OTC markets. The risk premium ebbs as different types of default fund calls flow into the clearinghouse. The aforementioned pushes down the premium. It does not, however, offset the upward effect stemming from the increasing recovery rate. Additionally, as the literature suggests that collateralization avoids default, t h e premium is high and the value of the position (or recovery rate) increases. In these contracts the risk premium is low too. This research contributes to the compression of insurance pricing theory into material that may be a critical input in large macroeconomic models.